A longitudinal study of individual differences in the acquisition of new vowel contrasts. (March 2018) - Kim, Donghyun; Clayards, Meghan; Goad, Heather
Highlights: Individual L2 learners differed in their cue weighting strategies over time. Individual differences in cue weighting were linked to their developmental trajectories. The developmental trajectories of individual learners varied according to vowel contrast. Adult learners had an initial advantage but some child learners made greater improvements. Abstract: This study explores how individuals' second language cue weighting strategies change over time and across different contrasts. The study investigates the developmental changes in perceptual cue weighting of two English vowel contrasts (/i/-/ɪ/ and /ɛ/-/æ/) by adult and child Korean learners of English during their first year of immersion in Canada. Longitudinal results revealed that adult learners had an initial advantage in L2 perceptual acquisition over children at least for the /i/-/ɪ/ contrast, but after one year some children showed greater improvements especially on the more difficult /ɛ/-/æ/ contrast. Both groups of Korean learners showed different acquisition patterns between the two vowel contrasts: they used both spectral and duration cues to distinguish /i/-/ɪ/ but generally only duration to distinguish /ɛ/-/æ/. By examining cue weights over time, this study partially confirmed the hypothesized developmental stages for the acquisition of L2 vowels first proposed by Escudero (2000) for Spanish learners of English. However, some unpredicted patterns were also identified. Most importantly, the longitudinal results suggest that individual differences in cue weighting are not merely random variability in the learner's response patterns, but are systematically associated with the developmental trajectories of individual learners and those trajectories vary according to vowel contrast.